The Influence of Eco-Brand, Eco-Labelling and Environmental Advertisement on Consumer Purchasing Behavior through Brand Image - Rizqiyana, Ina; Wahyono, Wahyono (Universitas Negeri Semarang, 2020)
The high level of environmental concern will encourage individual to consume environmentally friendly products and encourage company to implement the green marketing strategy. This study aims to examine the direct and indirect effect of green marketing tools namely eco-label, eco-brand and environmental advertisement on consumer purchase behavior with brand image as an intervening variable. The sampling method used is purposive sampling technique through questionnaire with 115 respondents who are consumers of Ades in Semarang. The data analysis method used is path analysis. The results of this study show that eco-brand and eco-labelling have positive and significant effect on consumer purchase behavior while environmental advertisement has negative and significant effect on consumer purchase behavior. Eco-brand, eco-labeling and environmental advertisement have positive and significant effect on consumer purchase behavior through brand image. Brand image has a role as an intervening variable between eco-brand, eco-labeling and environmental advertisement to consumer purchase behavior.